Supply chain planning considering the production of defective products - Ferrara, Miguel (2014)
When the markets become more competitive, the customer satisfaction level starts to be a more important factor. One of the principal components to achieve the customer satisfaction is to minimize the amount of defective or non-standard products. Therefore, it is convenient to consider decisions about product quality when the supply chain is planned. In this work, a mixed integer linear programming mathematical (MILP) model is developed for the supply chain planning, which determines impact of different decisions over the expected number of defective products. These decisions are: supplier selection, inbound control methods selection, and production process selection. The ob-jective function is the cost minimization associated to the supply chain planning.